2021
DOI: 10.3389/fsufs.2021.709993
|View full text |Cite
|
Sign up to set email alerts
|

Black Soldier Fly Diet Impacts Soil Greenhouse Gas Emissions From Frass Applied as Fertilizer

Abstract: Increased global production of animal-based protein results in high greenhouse gas (GHG) emissions and other adverse consequences for human and planetary health. Recently, commercial insect rearing has been claimed a more sustainable source of animal protein. However, this system also leaves residues called frass, which—depending on the insect diet—is rich in carbon (C) and nitrogen (N), and could thus be used as fertilizer in agriculture. The impact of this kind of fertilizer on soil GHG emissions is yet unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
(97 reference statements)
0
15
0
Order By: Relevance
“…Whether our results are generalizable might therefore depend on a generally high fiber content in BSFL residues compared to other organic fertilizers, which to our knowledge has not yet been assessed. The assumption is supported by recurrently highlighted stimulations of soil fungi after application of BSFL residues ( Temple et al, 2013 ; Rummel et al, 2021 ; Watson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…Whether our results are generalizable might therefore depend on a generally high fiber content in BSFL residues compared to other organic fertilizers, which to our knowledge has not yet been assessed. The assumption is supported by recurrently highlighted stimulations of soil fungi after application of BSFL residues ( Temple et al, 2013 ; Rummel et al, 2021 ; Watson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…d Calculated using a N fertilizer replacement value of 68% and a N to NH 4 NO 3 conversion factor of 2.9. e Calculated using a P to P 2 O 5 conversion factor of 2.3. f Calculated using a K to K 2 O conversion factor of 1.2. in larvae and frass, were obtained from and . Emissions from frass management are scarce in the literature, but we used those recently reported by Rummel et al (2021), who reported that on average 5.38% of the N in frass directly applied to soils is lost as N 2 O. It is worth to mention that frass can be composted prior to its use as a soil amendment, or directly applied to the soil without any prior composting.…”
Section: Assumptionsmentioning
confidence: 99%
“…It is worth to mention that frass can be composted prior to its use as a soil amendment, or directly applied to the soil without any prior composting. For our system, we assumed the later as it represented the measurements reported by Rummel et al (2021). We assumed that frass replaced the mineral fertilizer ammonium nitrate (NH 4 NO 3 for N, triple superphosphate for phosphorus pentoxide (P 2 O 5 ), and potassium chloride for potassium oxide (K 2 O).…”
Section: Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations